Critical Remarks about Environmentalism Implication by Iranian SMEs - Behjati, Saeed (European Journal of Sustainable Development, 2017)
The need of environmental sustainability, level up variety of environmental protection agenda and enhance global expectation despite of the countries levels of industrial development. This review paper, highlights the confronting situation and prime criteria required in implementing corporate environmentalism geared into national environmental sustainability. Postpositive inductive inquiry about environmental sustainability orientation of Iranian SMEs manufactures was conducted. Triangulated data source was obtained while interviews were from top executives of three purposefully selected SME’s of different industrial sectors. The emerging themes can consider as the informant pattern of thinking regarding the environmental sustainability matter in current situation; which are made up of existent unique crisis, undermined competitiveness, techniques and technical hinders, energy backwardness, government policies indices. Interpretation of finding revealed some critical factors that can be consider for substantial transformation towards corporate environmentalism. Keyword: Corporate Environmental Sustainability, Iranian Small and Medium Size Enterprise, Managerial Pattern of Thinking, Critical Factors